Enhancement of biological denitrification by the addition of novel sRNA Pda200 under antibiotic pressure. (December 2022) - Wang, Mei; Liang, Yi; Li, Fulin; Shen, Shuqing; Huang, Xinyu; Sun, Yongxue
Graphical abstract: Highlights: Pda200 is an sRNA responsive to multiple antibiotics. Consortium exhibited a higher denitrification performance under antibiotic pressure. Pda200 promoted the expression of genes napA, napB and norB in denitrifiers. Pda200 may be utilized as functional enhancer for different types of denitrifiers. Abstract: Paracoccus denitrificans can adapt to complex environmental changes and sRNAs play crucial roles during this process. This work aim to identify antibiotic-induced sRNA that regulated denitrification and explored its potential for functional enhancement of this process. Target prediction indicated complementary base pairing between the denitrifying gene nosZ and the sRNA Pda200. Anaerobic culture of P. denitrificans ATCC 19367 in the presence of florfenicol (FF) resulted in significant decreases in nosZ and Pda200 gene expression ( p  < 0.01). Two additional denitrifiers isolated from contaminated sediment were co-cultured with ATCC 19367 to generate a consortium. And an inducible Pda200 expression strain was also added. The results revealed that Pda200 significantly enhanced napA, napB and norB expression in different types of denitrifiers under FF condition ( p  < 0.05 ∼ 0.001). This study identified the sRNA Pda200 as a novel positive regulator of denitrification, which may realize the efficient treatment of antibiotic-contaminated wastewater by microbial agents.